Return to normal operations: COVID-19 mitigation strategies for workplaces. (September 2020) - Parker, Justine; Boles, Corey; Egnot, Natalie; Sundermann, Alexander; Fleeger, Alan
As spikes and resurgences of COVID-19 cases continue to increase in different geographical regions across the United States, more and more companies are left with numerous questions about reopening or restarting their operations. The current pandemic in the United States poses unique challenges unlike any other for businesses and employers as they begin to reopen. Businesses and employers are forced to ensure that they are not only in compliance with federal guidances but also with state and local guidances. In addition to the complex and ever evolving guidances, we are still learning about and adapting best practices during these reopening phases. Therefore, it is crucial for businesses to stay up-to-date not only with the released guidances but also with the latest understanding and information about SARS-CoV-2. As part of reopening, it is crucial for businesses to have comprehensive reopening plans prior to restart of operation. These plans must be clear, concise, and flexible enough to include updated guidances and information. In this publication, we describe reopening frameworks, considerations, and strategies that can be used as a starting point for businesses to further optimize and tailor to their unique operations.